2019
DOI: 10.3389/fmicb.2019.00667
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolite Dereplication and Phylogenetic Analysis Identify Various Emerging Mycotoxins and Reveal the High Intra-Species Diversity in Aspergillus flavus

Abstract: Aspergillus flavus is one of the most important mycotoxigenic species from the genus Aspergillus , due to its ability to synthesize the potent hepatocarcinogen, aflatoxin B 1 . Moreover, this fungus is capable of producing several other toxic metabolites from the class of indole-tetramates, non-ribosomal peptides, and indole-diterpenoids. Populations of A. flavus are characterized by considerable diversity in terms of morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 141 publications
3
22
0
Order By: Relevance
“…The extrolite patterns of the Aspergillus species, isolated and identified in this study, except A. tamarii which was not evaluated, are shown in Table 1. Members of the section Flavi produced metabolites (aflatoxins and their biosynthetic pathway precursors, asparason A, cyclopiazonic acid, desoxypaxillin, kojic acid, kotanin A, paspalin and paspalitrems) consistent with previous reports (Frisvad et al 2019, Uka et al 2019. However, some new findings are reported herein.…”
Section: Aspergillus Metabolitessupporting
confidence: 92%
See 1 more Smart Citation
“…The extrolite patterns of the Aspergillus species, isolated and identified in this study, except A. tamarii which was not evaluated, are shown in Table 1. Members of the section Flavi produced metabolites (aflatoxins and their biosynthetic pathway precursors, asparason A, cyclopiazonic acid, desoxypaxillin, kojic acid, kotanin A, paspalin and paspalitrems) consistent with previous reports (Frisvad et al 2019, Uka et al 2019. However, some new findings are reported herein.…”
Section: Aspergillus Metabolitessupporting
confidence: 92%
“…However, some new findings are reported herein. For example, desoxypaxillin, heptelidic acid, kotanin A and paspalitrems were previously reported in A. flavus (Uka et al 2019, Kovac et al 2020, but not in A. aflatoxiformans, A. austwickii and A. cerealis. Hence, we present the first report of desoxypaxillin, kotanin A (mean: 534 µg/kg) and paspalitrems in the three S-type sclerotium (minisclerotium) producing species and heptelidic acid (10.2 mg/kg) only in A. austwickii.…”
Section: Aspergillus Metabolitesmentioning
confidence: 92%
“…Four A. flavus strains were considered for metabolite profiling; three strains were aflatoxigenic while the DTO 481-G5 strain was non-aflatoxigenic but produced cyclopiazonic acid and kojic acid. The aflatoxigenic strains produced the B aflatoxins together with other known metabolites including 3-nitropropionic acid, aflatrem, aflavarins, asparason A cyclopiazonic acid, desoxypaxillin, kojic acid, kotanin A, paspalin and paspalitrems; Frisvad et al, 2019;Uka et al, 2019). We also found heptelidic acid in a culture of one aflatoxigenic A. flavus strain; this corroborates the findings of a previous study from our group wherein we reported this metabolite in both mycelia and culture media extracts of aflatoxigenic A. flavus (Kovač et al, 2020).…”
Section: Metabolites From Aspergillussupporting
confidence: 91%
“…It must be stressed that AFM 1 , which is mainly considered as a liver-hydroxylated metabolite of AFB 1 , was detected in the (Flav + ) extract. This direct production of AFM 1 by A. flavus was also recently reported by Uka et al [16], but does not appear to have been commonly described. A significant direct mutagenicity was observed in TA98 for (Flav + ) and (Para + ) extracts as well as for pure AFB 1 .…”
Section: Strains S9supporting
confidence: 84%
“…Moreover, the absence of mutagenicity for (Flav -) and (Para -) extracts could indicate that additional metabolites are closely related to the AFB 1 synthesis pathway. Recently, Uka et al [16] highlighted the particularly high intra-species diversity of A. flavus and reported the large variety of secondary metabolites that can be produced. Using a metabolomic approach on 55 isolates of A. flavus, they identified more than 50 metabolites even if only half of the 55 strains were considered as aflatoxin producers.…”
Section: Strains S9mentioning
confidence: 99%